Challenges in considering distributed generation in the analysis and design of distribution systems - Dugan, R.C. (2008 IEEE Power and Energy Society General Meeting - Conversion and Delivery of Electrical Energy in the 21st Century, 2008)
The state of the art in distribution system analysis is examined with respect to distributed generation (DG). The types of analysis required for DG evaluation are described briefly. Then 14 challenges with respect to this subject are described and areas ripe for further research are pointed out.